VsMATE1-Mediated Citrate Efflux Is Involved in Al Resistance in Common Vetch (Vicia sativa L.) - Wenhui Yan; Jia Shi; Ling He; Zigang Hou; Zhenfei Guo; Haifeng Zhu (Plants)
Planting aluminum-tolerant legume green manure is a cost-effective and sustainable method to increase soil fertility as well as decrease Al toxicity in acidic soils. By analyzing the relative root elongation of seven legume green manure species, common vetch (Vicia sativa L.) was identified as an Al-resistant species. Furthermore, cultivars 418 (cv. Sujian No.3) and 426 (cv. Lanjian No.3) were identified as Al-resistant and -sensitive cultivars, respectively, among 12 common vetch germplasms. The root growth of 418 was less inhibited by Al toxicity in both the germination stage and seedling stage than that of 426. Under Al toxicity, 418 accumulated less Al in both roots and shoots. Citrate is more abundant in the roots of common vetch compared to oxalate or malate. The internal citrate contents showed no significant difference between 418 and 426 under either control or Al treatment. However, the citrate efflux increased in response to Al in 418 but not in 426 and was higher in 418 under Al stress than in 426. Consistently, VsMATE1 expression increased faster and to a greater extent in 418 than 426 in response to Al stress. These results indicated that a VsMATE1-mediated citrate efflux might play an important role in Al resistance in common vetch. It is suggested that VsMATE1 is a valuable candidate gene for aluminum resistance breeding.